ANALYSIS OF FINANCIAL PERFORMANCE IN SOUTH KOREA MUSIC INDUSTRY COMPANIES: HYBE CORPORATION - Palondongan, Meysri; Mase, Ignasius Oscar; Mongan, Benyamin; Jaya, Amir; Halik, Markus (Journal of Entrepreneur, Business and Management, 2024)
The South Korean music industry is experiencing rapid development due to the Korean Wave that spread South Korean popular culture globally. This study aims to determine the financial performance of Hybe Corporation from 2018 to 2022. This research uses quantitative research. The data source used is secondary data obtained from Hybe Corporation's financial statements from 2018 to 2022 which include balance sheets and income statements obtained through the company's official website. The data analysis method uses financial ratios such as Liquidity Ratio, Solvency Ratio, and Profitability Ratio. The results showed that the liquidity ratio through the Current Ratio and Cash Ratio indicators was in quite good condition. Solvency Ratio through Debt Ratio and Debt to Equity Ratio indicators are in good condition. Profitability Ratio through indicators of Net Profit Margin, Return on Investment, and Return on Equity are in poor condition. As a result, Hybe Corporation's financial performance from 2018 to 2022 has not been optimal in managing its finances.Keywords: Financial Performance, Financial Ratios, Music Industry, Korean Wave